2022
DOI: 10.1038/s41419-022-04694-z
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate kinase L/R links metabolism dysfunction to neuroendocrine differentiation of prostate cancer by ZBTB10 deficiency

Abstract: Neuroendocrine differentiation (NED) frequently occurs in androgen-deprivation therapy (ADT)-resistant prostate cancer (PCa) and is typically associated with metabolic pathway alterations, acquisition of lineage plasticity, and malignancy. There is no conventional therapeutic approach for PCa patients with NED pathologic features because the molecular targets are unknown. Here, we evaluated the regulatory mechanism of NED-associated metabolic reprogramming induced by ADT. We detected that the loss of the andro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…Through the intersection analysis of transcription factors targeting HK1 and DEGs, ZBTB10 was screened out as the differently expressed transcription factor targeting HK1 (Figure 7A). It has been reported that ZBTB10 is involved in pyruvate kinase metabolism, which is a key process of the glycolysis response essential for cancer progression [28]. The RNA-seq results also revealed that the expression of the transcription factor ZBTB10 was elevated, and we confirmed that ZBTB10 mRNA and protein expression levels were elevated in both Hep2 and TU686 cells treated with conditioned medium, consistent with the RNA-seq results (Figure 7B-E).…”
Section: Resultssupporting
confidence: 90%
“…Through the intersection analysis of transcription factors targeting HK1 and DEGs, ZBTB10 was screened out as the differently expressed transcription factor targeting HK1 (Figure 7A). It has been reported that ZBTB10 is involved in pyruvate kinase metabolism, which is a key process of the glycolysis response essential for cancer progression [28]. The RNA-seq results also revealed that the expression of the transcription factor ZBTB10 was elevated, and we confirmed that ZBTB10 mRNA and protein expression levels were elevated in both Hep2 and TU686 cells treated with conditioned medium, consistent with the RNA-seq results (Figure 7B-E).…”
Section: Resultssupporting
confidence: 90%
“…Our previous report has demonstrated the upregulation of neuroendocrine marker expression in androgen‐dependent LNCaP cells treated with long‐term MDV3100 [ 41 , 42 ]. Our findings are consistent with other studies that used the same cells under similar culture conditions [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…S2C) is supportive of the notion that ARIP4 participates in the AR signaling pathway. Androgen-driven AR target genes include secreted proteins [kallikrein related peptidase 2 ( KLK2 ) and 3 ( KLK3 ); markers for prostate cancer screening and prognosis ( 30 , 31 )], proto-oncogenes { TMPRSS2 when fused with ERG ( 5 ) and growth factors [insulin-like growth factor 1 receptor ( 32 )]}, modulators of phosphatidylinositol 3-kinase (PI3K)/Akt and Notch signaling [ FKBP5 ( 33 ) and JAG1 ( 34 )], and transcription factors/tumor suppressors [NK3 Homeobox 1 ( NKX3.1 ) ( 35 , 36 ), ZBTB10 ( 37 ), and ZBTB16 ( 38 )]. Together, many AR target genes affected by loss of ARIP4 have been shown to promote prostate cancer growth, survival, and advancement ( 39 , 40 ), corroborating the important role of ARIP4 in conferring survival advantage (fig.…”
Section: Resultsmentioning
confidence: 99%